Frustrated Magnetism in Triangular Lattice TlYbS2 Crystals Grown via Molten Flux - Ferreira, Timothy; Xing, Jie; Sanjeewa, Liurukara D.; Sefat, Athena S. (Frontiers in Chemistry, 2020)
The triangular lattice compound TlYbS2 was prepared as large single crystals via a molten flux growth technique using sodium chloride. Magnetic susceptibility measurements down to 0.4 K indicate a complete absence of long-range magnetic order. Despite this lack of long-range order, short-range antiferromagnetic interactions are evidenced through broad transitions, suggesting frustrated behavior. Variable magnetic field measurements reveal metamagnetic behavior at temperatures ≤ 2 K. Complex low temperature field-tunable magnetic behavior, in addition to no observable long-range order down to 0.4 K suggests that TlYbS2 is a frustrated magnet and a possible quantum spin liquid candidate.